To apply the Distributive Property to multiply \((x - 5)(x - 1)\), we need to distribute each term in the first binomial to each term in the second binomial.
-
Multiply \(x\) by both terms in the second binomial: \[ x \cdot x = x^2 \] \[ x \cdot (-1) = -x \]
-
Multiply \(-5\) by both terms in the second binomial: \[ -5 \cdot x = -5x \] \[ -5 \cdot (-1) = 5 \]
Now combine all the results: \[ x^2 - x - 5x + 5 \]
Combine like terms: \[ x^2 - 6x + 5 \]
Thus, the final answer is: \[ \boxed{x^2 - 6x + 5} \]